Revelando las compras impulsivas en línea en plataformas de comercio electrónico durante el Ramadán: el rol de la informatividad, la confianza, la lealtad actitudinal y el autocontrol - Yeassy Kurniasari, Juwita (2025)
The swift expansion of e-commerce in Indonesia has altered consumer behavior, particularly given the prominence of platforms like Shopee and Tokopedia. This study seeks to examine the correlation between the online shopping experience, attitudinal loyalty, and impulsive buying habits during Ramadan. We employed a quantitative methodology to investigate the impact of informativeness and trust as functional and psychological elements of the online buying experience. Data were gathered from Shopee and Tokopedia users in Jakarta during Ramadan in 2025. The analysis reveals that factors such as informativeness and trust have a positive impact on online impulsive buying, with attitudinal loyalty acting as a mediating variable and self-control serving as an adverse moderating factor. Enhancing informativeness and trust can elevate loyalty and impulsive buying, while self-control diminishes the propensity for such behavior.